Analisis Makna Leksikal dan Gramatikal dalam Surat Kabar Tabangun Aceh Edisi 7 Desember2023 - Aritonang, Juwita Pratiwi; Sari, Mei Artika; Amna, Nailul; Ulfa, Nada; Daulay, Nirina Nabila Mumtaz; Sulistiani, Wiwi (Multiverse: Open Multidisciplinary Journal, 2024)
This study investigates the use of lexemes that carry lexical and grammatical meanings and examines how both contribute to meaning construction in the Tabangun Aceh newspaper, December 7, 2023 edition. As essential tools for disseminating information, newspapers—both print and digital—hold a significant place in public communication. However, the interpretation of news headlines is often influenced by ambiguous word choices, leading to multiple readings. This issue stems largely from the interplay between lexical and grammatical meaning, which may not always align clearly within journalistic language. Employing a qualitative research approach with a documentation method, this study draws data from digital newspaper texts. The analysis focuses on identifying and interpreting lexical units and syntactic structures that lead to ambiguity or misinterpretation. The findings reveal that lexical meaning, when not supported by appropriate grammatical context, can obscure intended messages and influence reader perception. Thus, the clarity of language in media discourse depends not only on vocabulary but also on how grammatical structures shape the delivery of information. The study underscores the importance of linguistic precision in the formulation of news headlines to ensure effective communication.